2022
DOI: 10.1111/bjd.21777
|View full text |Cite
|
Sign up to set email alerts
|

Living with vulval lichen sclerosus: a qualitative interview study

Abstract: Background Vulval lichen sclerosus (VLS) is a chronic inflammatory condition predominantly affecting the anogenital skin. Symptoms can be distressing and affect quality of life and everyday activities. Very little research has been undertaken to explore the experience of living with VLS from the perspective of people with the condition. Objectives To understand individuals’ experiences of VLS and its impact on their lives. Participants and methods Semi‐structured remote (telephone or video) interviews were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…Furthermore, depression was found to be connected with lower sexual quality of life [ 15 ]. In a qualitative interview study vulvar lichen sclerosus was described as a high maintenance disease that caused numerous changes in patients’ lives [ 29 ]. This illustrates the complexity of the disease and challenges with its management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, depression was found to be connected with lower sexual quality of life [ 15 ]. In a qualitative interview study vulvar lichen sclerosus was described as a high maintenance disease that caused numerous changes in patients’ lives [ 29 ]. This illustrates the complexity of the disease and challenges with its management.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies concerning vulvar dermatosis showed that there is still a lot od secrecy and stigma around vulvar diseases. Women often complained about shame and loneliness, lack of information and support [ 29 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It typically causes intense pruritus, fissures, and dyspareunia, and untreated can lead to malignancy and progressive changes to vulval architecture. Vulval lichen sclerosus can have a serious impact on quality of life, including loss of self-identity, shame, and stigma 4–7 . First-line treatment for VLS is ultrapotent topical corticosteroids (TCSs) which, in most cases, relieves symptoms and reverses skin color to normal 1,2,8 .…”
mentioning
confidence: 99%
“…While the current literature on VLS is quantitative, Arnold et al use a qualitative approach, which provides an in-depth exploration of the impact of VLS on the lives of individuals. 3 As reported in this issue of the BJD, 20 semistructured interviews were assessed to deepen understanding of the impact of VLS on an individual's quality of life. Thus, deficiencies in current clinical practice were identified to help healthcare professionals more efficiently treat and support people with VLS.…”
mentioning
confidence: 99%
“…Vanitha Sivalingam iD 1,2 and Kajal Tamber iD 3 1 The University of Manchester, Division of Cancer Sciences, Manchester Academic Health Science Centre, Manchester, UK; 2 The Christie NHS Foundation Trust, Department of Surgery, Manchester, UK and 3 Central Manchester University Hospitals NHS Foundation Trust, Manchester, UK Email: vanitha.sivalingam@manchester.ac.uk Conflicts of interest: the authors declare they have no conflicts of interest.…”
mentioning
confidence: 99%